2021
DOI: 10.1093/burnst/tkaa037
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for tissue expander infection in scar reconstruction: a retrospective cohort study of 2374 consecutive cases

Abstract: Background Tissue expansion is used for scar reconstruction owing to its excellent clinical outcomes; however, the complications that emerge from tissue expansion hinder repair. Infection is considered a major complication of tissue expansion. This study aimed to analyze the perioperative risk factors for expander infection. Methods A large, retrospective, single-institution observational study was carried out over a 10-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…According to other researches, patients may also encounter kinds of problems or complications, such as infection, extrusion, wound dehiscence and ruptures. 36 The prevention of infection could be managed with an algorithm put forward by Dong et al 37 Nevertheless, we did not observe any complications directly related to the transferred ap, like necrosis or infection, except for two cases of leakage during the gradual process of tissue expansion. Radwan et al 38 attributed the occurrence of leakage to 3 reasons: (1) inadvertent puncture of the tubing or the prosthesis; (2) improper securing of the connector; (3) use of an appropriate needle into the injection port.…”
Section: Discussionmentioning
confidence: 73%
“…According to other researches, patients may also encounter kinds of problems or complications, such as infection, extrusion, wound dehiscence and ruptures. 36 The prevention of infection could be managed with an algorithm put forward by Dong et al 37 Nevertheless, we did not observe any complications directly related to the transferred ap, like necrosis or infection, except for two cases of leakage during the gradual process of tissue expansion. Radwan et al 38 attributed the occurrence of leakage to 3 reasons: (1) inadvertent puncture of the tubing or the prosthesis; (2) improper securing of the connector; (3) use of an appropriate needle into the injection port.…”
Section: Discussionmentioning
confidence: 73%
“…According to other researches, patients may also encounter kinds of problems or complications, such as infection, extrusion, wound dehiscence and ruptures 38 . The prevention of infection could be managed with an algorithm put forward by Dong et al 39 . Nevertheless, we did not observe any complications directly related to the transferred flap, like necrosis or infection, except for two cases of leakage during the gradual process of tissue expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study found that a haemotoma offers an ideal medium for bacterial proliferation and greatly increases the possibility of expander infection. 32 Remote incision, far from the stress of the expansion, also minimizes the chances of wound dehiscence. 12 Whether the risks of extrusion and de ation can be reduced by the endoscopic technique remain controversial.…”
Section: Discussionmentioning
confidence: 99%